The British chalk specialist Lecidea lichenicola auct. revealed as a new genus of Lichinomycetes. Issue 7 (July 2021) - Díaz-Escandón, David; Hawksworth, David L.; Powell, Mark; Resl, Philipp; Spribille, Toby
Abstract: The lichen, to which the name Lecidea lichenicola is found to have been misapplied, was first described from England and is an extreme specialist of chalk pebbles. It has long been known that it is not closely related to Lecidea in the strict sense, but its true evolutionary relationships have been unknown. Here we use metagenome-assembled genome data to place this fungus in a six-locus phylogeny of Ascomycota, and find strong support for its placement in the class Lichinomycetes . Multiple gene trees using existing data from Lichinomycetes support its further placement within the family Lichinaceae . Based on a revision of types and original descriptions, we conclude that the earliest name for this species is Lecidea obsoleta (syn. Thrombium cretaceum ). We neotypify that name by a modern collection and accommodate it in the new genus Watsoniomyces. Type and other original material of L. lichenicola (syn. Discocera lichenicola ) was re-examined and found not to be on chalk and to represent a different lichen, Trapelia glebulosa . Watsoniomyces is the first described member of Lichinomycetes with an endolithic thallus.